Implementasi Sistem Pengendalian Manajemen dalam Meningkatkan Kinerja Karyawan pada Industri Tahu Afifah Palu - Nur Indah; Nayla Ramadani; Risky Polimengo; Wulandari L; Ernawaty Usman (CV. Doki Course and Training, 2026)
This study aims to analyze the implementation of a management control system in improving employee performance at Afifah Tofu Industry in Palu. The research employed a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving the business owner, operational manager, administration and finance staff, production staff, marketing and distribution staff, employees, and regular customers. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that the implementation of the management control system has been carried out effectively through market demand-based production planning, direct and indirect supervision, periodic performance evaluation, the application of a reward and punishment system, the implementation of Standard Operating Procedures (SOPs), and the utilization of technology in the production process. The implementation of these systems has positively contributed to improving employee productivity, discipline, and work quality. However, challenges remain, particularly regarding the low level of discipline among some employees, which may affect the effectiveness of the management control system. This study concludes that the management control system implemented by Afifah Tofu Industry plays a significant role in supporting employee performance improvement and enhancing the company's operational effectiveness. Abstrak Penelitian ini bertujuan untuk menganalisis implementasi sistem pengendalian manajemen dalam meningkatkan kinerja karyawan pada Industri Tahu Afifah Palu. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi yang melibatkan pemilik usaha, manajer operasional, bagian administrasi dan keuangan, bagian produksi, bagian pemasaran dan distribusi, karyawan, serta pelanggan tetap. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi sistem pengendalian manajemen telah berjalan cukup baik melalui penerapan perencanaan produksi berbasis permintaan pasar, pengawasan langsung dan tidak langsung, evaluasi kinerja secara berkala, sistem reward dan punishment, penerapan standar operasional prosedur (SOP), serta pemanfaatan teknologi dalam proses produksi. Implementasi sistem tersebut memberikan dampak positif terhadap peningkatan produktivitas, disiplin, dan kualitas kerja karyawan. Namun demikian, masih ditemukan kendala berupa rendahnya tingkat kedisiplinan sebagian karyawan yang dapat memengaruhi efektivitas sistem pengendalian manajemen. Penelitian ini menyimpulkan bahwa sistem pengendalian manajemen yang diterapkan Industri Tahu Afifah berperan penting dalam mendukung peningkatan kinerja karyawan dan efektivitas operasional perusahaan.